Compounds isolated at the Department of Biogenesis of Natural Substances, Institute of Microbiology, Czechoslovak Academy of Sciences, in 1984-1988 - Podojil, M; Cudlín, J (Folia microbiologica, 1989)
A total of 41 compounds studied at the Department of Biogenesis of Natural Substances between 1984 and 1988 are characterized and tabulated. They include natural, semisynthetic and synthetic compounds.
Keywords: Ergot Alkaloids; námelové alkaloidy; monensin; Bacteria; Monensin